Interconnectedness and contagion analysis - Bricco, Jana,Xu, TengTeng (International Monetary Fund, 2019)
The analysis of interconnectedness and contagion is an important part of the financial stability and risk assessment of a country's financial system. This paper offers detailed and practical guidance on how to conduct a comprehensive analysis of interconnectedness and contagion for a country's financial system under various circumstances. We survey current approaches at the IMF for analyzing interconnectedness within the interbank, cross-sector and cross-border dimensions through an overview and examples of the data and methodologies used in the Financial Sector Assessment Program. Finally, this paper offers practical advice on how to interpret results and discusses potential financial stability policy recommendations that can be drawn from this type of in-depth analysis
10.5089/9781513516226.001
Keywords: Graue Literatur; Banks and Banking; Finance: General; General Financial Markets: Government Policy and Regulation; Banks; Depository Institutions; Micro Finance Institutions; Mortgages; Financial Institutions and Services: Government Policy and Regulation; Finance; Financial Sector Assessment Program; Financial contagion; Banking; Systemic risk; Commercial banks; Financial sector policy and analysis; Financial institutions; Stress testing; Financial risk management; Banks and banking; Financial services industry; Interconnectedess; Contagion; Financial Stability; Financial Systems; Risk Analysis; Systemic Risk